Engaging undergraduate students in research for disaster mitigation on campus - Ritchie, Michelle A.; Acosta Chaves, Daniel; Milledge, Phoebe L.; Knight, Isabel; Stein, Scott; Joseph, Libin; Morris, Ashley; Smith, Jada (International Journal of Disaster Management, 2025)
Disasters can incur risks to life, property, and the environment, whether caused by natural, human-made, or technological hazards. However, mitigating some risks through effective planning and preparedness can lower exposure and vulnerability. Risk mitigation is particularly essential at institutions of higher education (IHE), where transient populations may be at greater risk. Thus, our study aimed to assess the disaster preparedness of a campus community at an IHE in the United States. We also aimed to identify strategies to support effective hazard mitigation planning and preparedness, the results of which may help foster a culture of preparedness on campus. To do this, undergraduate students developed and deployed a campus questionnaire to assess public risk perception and disaster preparedness. The questionnaire results (n=470) indicated a need for enhanced enrollment in emergency alert systems, more comprehensive disaster training, and increased awareness of campus hazards among the campus community, including visitors unfamiliar with the campus. Students used these results to develop hazard mitigation strategies, which they then presented and discussed with campus stakeholders at an end-of-semester stakeholder summit. Through this process, students directly engaged in disaster preparedness on campus. This study highlights the importance of fostering disaster preparedness at IHEs by assessing the campus community's perceptions and preparedness levels by engaging students in active learning to promote disaster risk reduction.